IMPLEMENTASI KURIKULUM MERDEKA BELAJAR TERHADAP LAYANAN BIMBINGAN DAN KONSELING PADA PENGEMBANGAN DIRI DI SMAIT UKHUWAH BANJARMASIN - Irfan, Irfan; Muhammad Yuliansyah,; Sanusi, Sanusi (Journal of Innovation Research and Knowledge, 2025)
This research aims to analyze: (1) Implementation of the independent learning curriculum towards counseling guidance services for self-development at SMAIT Ukhuwah Banjarmasin. (2) Obstacles and efforts taken to overcome various problems in implementing the independent learning curriculum regarding guidance and counseling services for self-development at SMAIT Ukhuwah. The method used in this research is qualitative method. Data collection techniques through interviews, observation, documentation. The results of the analysis show that the form of implementing the independent learning curriculum is (1) the guidance and counseling teacher is assigned to be a P5 facilitator (project to strengthen the profile of Pancasila students) and actively participates in assisting students' self-development activities in schools starting from grade 10 to grade 12 in preparation for further study. (2) The SNBP (Achievement Based National Selection) graduation results for the independent curriculum class have decreased compared to the 13curriculum class due to the SNBP system not fully accommodating schools that implement the Independent curriculum.